Dilema Biaya Pesantren yang Mahal: Hambatan Orang Tua dalam Menyelamatkan Pendidikan Agama Anak - Sintia, Sela; Agustin, Selsi; PutriPutri, Umil Khairi; Yahya, Muhamad (TSAQOFAH, 2026)
Islamic boarding schools (pesantren) have long been trusted educational institutions for cultivating children’s religious and moral character; however, in recent years rising educational costs have created a dilemma for parents, particularly those from lower-middle-income families. This study aimed to analyze the high cost of pesantren education as a major barrier for parents in providing religious education for their children, to identify the social and educational impacts of this condition, and to formulate alternative solutions so that pesantren remain affordable for diverse social groups. The research employed a qualitative descriptive approach, with data collected through in-depth interviews, observation, and documentation. Respondents consisted of parents who wished to enroll their children in pesantren but were constrained by costs, pesantren administrators, and community leaders. The findings indicate that most parents had a strong desire to send their children to pesantren to obtain more intensive religious education, yet they were burdened by high initial fees reaching millions of rupiah, alongside mandatory monthly payments, equipment costs, and other additional fees. This situation has become a primary factor preventing lower-middle-income families from accessing pesantren education and has simultaneously created a dilemma in determining priorities for their children’s education. The study concludes that more inclusive planning and policy are needed so that pesantren can become more open and affordable, thereby enhancing equitable public access to high-quality religious education.